Molecular docking study of Indonesian phytochemicals as inhibitor of 6-HB formation by binding to HR1 subunit of SARSCOV-2 S2 protein - Julianus, Jeffry; Phebe Hendra; Maywan Hariono; Nico Frederick; Satrio Ardyantoro; Mustofa; Jumina (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Coronavirus disease 2019 (COVID-19) is still as global pandemic. No officially drugs to treat COVID-19 are available until now. Increasing number of patients and deaths trigger new antiCOVID-19 discovery efforts. In this study, we have conducted in silico screening employing molecular docking for Indonesian phytochemicals. Docking process was performed by employing AutoDock4 software on crystal structure 6VSB. Based on molecular docking results, several compounds had potential as antiCOVID-19 drugs, such as β-carotene, veramiline, ecliptalbine, betulinic acid, and lupeol. β-carotene was the most potential compound to treat COVID-19.